Fine needle aspiration cytology as a first line investigation in cervical swellings of 470 cases - Gamit, Bhavna G.; Patel, Mubin I.; Patel, Mandakini M.; Patel, Sharmistha M. (International Journal of Research in Medical Sciences, 2018)
Background: Fine needle aspiration cytology (FNAC) is a first line investigation in cervical swellings. The etiology varies from an inflammatory process to a malignant condition. Methods: The study was carried out in department of Pathology, Government Medical College, affiliated with government hospital in Gujarat. There were 470 patients with cervical swelling in a period from January 2017 to December 2017. Patients with thyroid swelling (swelling moves with deglutition) were excluded from the study. FNAC procedure was performed, smears prepared, stained with haematoxylin and eosin (H and E), May Grunwald Giemsa (MGG) and Pap stain. Zeihl Neelsen stain was carried out when required. Patient history, local examination findings and microscopic findings were recorded. Results: Total 470 patients, age ranged from 2 months to 90 years were studied. There were 286 males and 184 females. There were 449 cases in which conclusive opinion given. 111 cases were neoplastic and 338 cases were non-neoplastic. Various cytological diagnosis were; 207 cases of granulomatous lymphadenitis (tuberculosis), 1 case of filarial lymphadenitis, 72 cases of chronic reactive hyperplasia, 25 cases of acute suppurative inflammation, 1 case of sialadenitis, 10 cases of keratinous cyst, 6 cases of benign cystic lesion, 12 cases of lipoma, 4 cases of lymphoproliferative lesion, 1 cases of benign appendage tumor, 2 cases of mucoepidermoid carcinoma, 103 cases of metastasis and 5 cases of non Hodgkin lymphoma. Conclusions: FNAC is a simple, quick, inexpensive and minimally invasive technique to diagnose cervical swellings. It can differentiate the infective process from neoplastic one and avoids unnecessary surgeries.